複合構造物を活用した既設鉄道RC高架橋のリニューアル手法に関する基礎的研究 - 斉藤, 雅充; 谷口, 望; 西村, 昌宏; 桜井, 淳; 上村, 寿志; 依田, 照彦; 北川, 淳一 (構造工学論文集 Ａ, 2013)
Some of existing railway RC viaducts have insufficient seismic performance, and the spaces under them are limited. To ensure the seismic performance and improve the space utilization, a renewal method by installing additional hybrid columns and removing existing columns was proposed. In this study, loading tests of the connection between the additional column and the existing beam were carried out in order to clarify the seismic performance and workability. As a result, it was clarified that the connection has enough seismic performance under the condition that the mortar is appropriately filled between the steel jacket and the existing beam. Appropriate mortar liquidity and filling space were also confirmed in the tests.